2019
DOI: 10.1007/s10389-019-01084-2
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake and its correlates among high-school adolescents in Iran: a cross-sectional study

Abstract: Background Two important components of a healthy diet are fruits and vegetables (F&V), which are essential for maintaining physical health. The aim of the present study was to assess the prevalence and correlates of F&V intake among high school adolescents in the city of Tabriz. Methods The Global School-based Student Health Survey self-administered questionnaire was used for data collection among 1517 adolescents. Results The prevalence of fruit intake was 76.1% (≥ 2 times/day) and vegetable intake 23% (≥ 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
1
4
1
1
Order By: Relevance
“…al also stated parental and peer supports are two important factors that affect adolescents' F&V intake and healthy eating habits. 14,32 In terms of F&V knowledge level in teenagers, the results are also similar to previous studies which showed that the proportion of teenagers with good F&V consumption was found higher in the group with good nutritional knowledge. 14,16 The results of statistical tests showed that there was a significant relationship between F&V consumption and F&V accessibility (p=0.016) which is in line with the study by Trofholz, et.…”
Section: Discussionsupporting
confidence: 89%
“…al also stated parental and peer supports are two important factors that affect adolescents' F&V intake and healthy eating habits. 14,32 In terms of F&V knowledge level in teenagers, the results are also similar to previous studies which showed that the proportion of teenagers with good F&V consumption was found higher in the group with good nutritional knowledge. 14,16 The results of statistical tests showed that there was a significant relationship between F&V consumption and F&V accessibility (p=0.016) which is in line with the study by Trofholz, et.…”
Section: Discussionsupporting
confidence: 89%
“…In this way, F&V intake as a health behaviour as well is influenced by a series of psychological, social and structural factors leading to certain beliefs and choices ( 40 ) . Considering people make food choices about 220 times a day ( 55 ) , targeting individual, interpersonal and environmental factors to increase fruit and vegetable intake should be a priority for public health interventions ( 56 ) . On the other hand, the value of educational programmes also depends on their effectiveness based on the appropriate utilisation of theories and models ( 48 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Kelebihan berat badan ataupun obesitas pada remaja berkaitan dengan konsumsi buah dan sayur yang rendah, pengaruh teman sebaya, serta kurangnya aktivitas fisik (8). Penelitian pada remaja di Brazil Selatan diketahui bahwa 14,3% memiliki kelebihan berat badan dan 8,8% termasuk dalam kriteria obesitas.…”
Section: Pendahuluanunclassified